Late adolescent primary nocturnal enuresis: a case report - Selvaraj, Periyar Rani; Thirumalai, Ranganathan (International Journal of Research in Medical Sciences, 2017)
Primary nocturnal enuresis is a rare condition. Literature review revealed that 1% of boys still bed wet at 17 years of age. There is a paucity of literature on the incidence and prevalence of bed wetting in patients above 17 years of age. We therefore present a case of 18-year-old boy having bed wetting since childhood.